Proceedings of the International Conference on Science and Education and Technology 2018 (ISET 2018) 2018
DOI: 10.2991/iset-18.2018.64
|View full text |Cite
|
Sign up to set email alerts
|

Application of Android-Based Stress Meter as Stress Academic Indicator on College Student with Low Achievement Motivation

Abstract: Academic stress on college students often triggers a low level of achievement motivation for students. Today in the digital age, psychological measurement instruments are needed that can be quickly, effectively and efficiently used by college counselors. Based on this, it is necessary to apply an Android-based stress measurement instrument. The research for this initial study aims to implement in a limited area of Android version of stress measurement instruments with an acceptable level of acceptability crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Several previous studies have shown that the use of stress assessment instruments Android-based can measure levels of depression, anxiety and stress and is good for implementation [19] [33]. Android is a mobile application that is quite popular because of the speed factor, namely the efficiency of the application in providing data according to the user's wishes [34]. It's just that there is a weakness in using web-based Android, namely that its use is very dependent on the availability of a good and stable internet network to access the applications being created [35].…”
Section: Table 9 Analysis Of Trials With System Usability Scale (Sus)mentioning
confidence: 99%
“…Several previous studies have shown that the use of stress assessment instruments Android-based can measure levels of depression, anxiety and stress and is good for implementation [19] [33]. Android is a mobile application that is quite popular because of the speed factor, namely the efficiency of the application in providing data according to the user's wishes [34]. It's just that there is a weakness in using web-based Android, namely that its use is very dependent on the availability of a good and stable internet network to access the applications being created [35].…”
Section: Table 9 Analysis Of Trials With System Usability Scale (Sus)mentioning
confidence: 99%